Is Strategic and Sustainable Leadership Synonymous With Effective Leadership? - Saiti, Anna (Journal of Leadership, Accountability and Ethics, 2021)
The purpose of this study is, after a thorough analysis of the relevant literature, to investigate whether strategic/sustainable leadership and effective leadership – key concepts for the educational sector – are synonymous or whether they complement each other, and indeed whether there is an interdependence between these concepts of leadership. The effectiveness of the school (and any organization) depends on the efficient use of available resources and on the implementation of strategic/sustainable leadership. Τhe coexistence of all members in the school’s leadership and the creation of collaborative social networks are the basic elements for establishing school sustainability.